2015
DOI: 10.1016/j.neures.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Blink-related dynamic switching between internal and external orienting networks while viewing videos

Abstract: Humans spontaneously generate eyeblinks every few seconds. However, because this blink rate is several times more common than is required for ocular lubrication, the function of most spontaneous eyeblinks remains unknown. Because spontaneous eyeblinks tend to occur at implicit breakpoints in video stories, I hypothesized that spontaneous eyeblinks play an active role in attentional disengagement from external stimuli. Consistent with this, we previously found that spontaneous eyeblinks involve the concurrent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…A previous fMRI study examining the effect of spontaneous blinking while viewing videos also reported blink-related activation of the bilateral hippocampal regions (Nakano, 2015). This is in line with the blink-related parahippocampal activations and theta-band effects observed in this study, as theta oscillations are known to be associated with hippocampal and parahippocampal activity, particularly in the context of memory-related processes (Buzsáki, 2002;H.…”
Section: Bro-related Spectral Differences Under Cognitive Loadingsupporting
confidence: 91%
See 1 more Smart Citation
“…A previous fMRI study examining the effect of spontaneous blinking while viewing videos also reported blink-related activation of the bilateral hippocampal regions (Nakano, 2015). This is in line with the blink-related parahippocampal activations and theta-band effects observed in this study, as theta oscillations are known to be associated with hippocampal and parahippocampal activity, particularly in the context of memory-related processes (Buzsáki, 2002;H.…”
Section: Bro-related Spectral Differences Under Cognitive Loadingsupporting
confidence: 91%
“…In other words, the brain must act earlier to prepare itself to process blink-related information during high cognitive loading conditions. Moreover, EEG also has inherent limitations due to electrical field distortions in volume conduction (Nunez et al, 1994), while MEG is much less susceptible to this effect given that the propagation of magnetic fields is not impacted by differences in tissue conductivity (Marinova & Mateev, 2010 A previous fMRI study examining the effect of spontaneous blinking while viewing videos also reported blink-related activation of the bilateral hippocampal regions (Nakano, 2015). Similarly, the earlier offset of the alpha ERD in the left posterior precuneus during MA may represent the brain's attempt to quickly complete any blink-related processing in order to return to the cognitive task at hand.…”
Section: Bro-related Spectral Differences Under Cognitive Loadingmentioning
confidence: 99%
“…They found that blinks tend to occur at what the authors describe as 'breakpoints' or points in time coinciding with event boundaries such as a pause in speaking or the end of a sentence while reading (Nakano et al, 2013). The blink related changes in brain activity reported by Nakano et al (2013), Nakano (2015) reveal richer detail in the changes in brain activity associated with blink related event boundaries. Specifically, brain activity increases immediately following blinks were primarily restricted to the default mode network (DMN), including the hippocampus while activity in the dorsal attention network, a task positive network, was reduced (Nakano et al, 2013, Nakano, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while increases in brain activity have been observed to coincide with the occurrence of consciously identified event boundaries, there may be other events that are processed as event boundaries but are not consciously recognized as such. Nakano et al (2013), Nakano (2015) examined the brain activity correlates of blinks. They found that blinks tend to occur at what the authors describe as 'breakpoints' or points in time coinciding with event boundaries such as a pause in speaking or the end of a sentence while reading (Nakano et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation